Perkembangan Dan Dampak Industri Fintech Peer To Peer Lending (P2P) Terhadap Bank Umum Konvensional Di Indonesia - Dendy Kurniansyah (Universitas Mercu Buana, 2019)
In 2018, the number of registered or licensed Financial Technology Peer to Peer Lending (P2P) companies increased by 203.45% to become 88 companies compared to last year, consisting of 86 conventional Companies and two companies conducting business activities with Islamic principles, disbursing a total of Rp. 22.7 trillion, skyrocketing 808% (YoY) on the Rp. 2.5 trillion recorded in the previous period. Pursuant to the location of the company profile, Fintech Peer to Peer Lending (P2P) in Indonesia is mostly developed in Jabodetabek and 70.45% is owned by domestic capital. OJK will facilitate and monitor the progress of Fintech’s start-up, including the start-up of Fintech Peer-to-Peer Lending and Equity Crowdfunding through a conducive regulatory framework to encourage innovation and, at the same time, provide adequate consumer protection. In addition, together with relevant institutions and agencies, OJK continues to increase community literacy towards Fintech and strengthen law enforcement for the start-up of illegal Fintech that harms the public.